HALAL COMPLIANCE IN ISLAMIC ECONOMIC LAW: A SHARIA QUALITY MANAGEMENT LENS - Muhammad Zaki (JURNAL HAKAM, 2025)
Halal certification has been institutionalized in Indonesia as a legal obligation for business actors, including micro-enterprises, to ensure halal assurance and consumer protection. However, its implementation, particularly through the self-declare certification scheme, continues to encounter challenges at the local level. This study aims to analyze the perceptions and barriers experienced by micro-enterprises in fulfilling halal certification requirements from the perspective of Islamic Economic Law using a Sharia Quality Management approach. Employing a qualitative case study design, this research was conducted in Bungo Regency, Jambi Province, with data collected through in-depth interviews involving seven micro-enterprise actors in the food sector who were undergoing or had completed the self-declare certification process. The data were analyzed thematically by linking empirical findings to the principles of muamalah, maqāṣid al-sharīʿah, and rafʿ al-ḥaraj. The findings indicate a very high level of normative acceptance of mandatory halal certification as a religious and legal obligation; however, implementation remains constrained by structural barriers, including difficulties in verifying locally sourced raw materials, uncertainty in certification timelines extending up to approximately five months, limited digital accessibility due to rigid systems, and hidden costs in the form of time loss and administrative burdens. These conditions raise concerns regarding legal certainty, potential hardship, and inequality of access to legal compliance. This study concludes that the effectiveness of halal certification should be assessed not only through formal compliance but also through the quality of its implementation in ensuring justice, accessibility, and maṣlaḥah for micro-enterprises within the framework of Islamic Economic Law.